2022
DOI: 10.1016/j.ygyno.2022.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction pathway activity in high-grade serous carcinoma, its precursors and Fallopian tube epithelium

Abstract: Aberrant PI3K, HH and ER pathway activity might be putative early drivers of neoplastic transformation of FTE into STIC.• STIC and concurrent HGSC showed loss of FOXO3a protein expression in comparison to normal FTE.• Loss of AR and Wnt pathway activity are more likely to be contributors of HGSC progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It has been found that neoplastic transformation of the fallopian tube epithelium into STIC and further disease progression are accompanied by abnormal functioning of several signaling pathways. Hypoactivation of estrogen receptor (ER) and hyperactivation of Hedgehog and PI3K/AKT/mTOR signaling cascades are involved in a transition to neoplasia, while the decreased activity of androgen receptor (AR) and Wnt pathways contribute to disease progression [ 111 ]. Detailed recognition of pathologic signaling at the molecular level provides the mechanistic background for novel therapeutic approaches ( Figure 3 ).…”
Section: Signal Transduction Pathways As Potential Therapeutic Targetsmentioning
confidence: 99%
“…It has been found that neoplastic transformation of the fallopian tube epithelium into STIC and further disease progression are accompanied by abnormal functioning of several signaling pathways. Hypoactivation of estrogen receptor (ER) and hyperactivation of Hedgehog and PI3K/AKT/mTOR signaling cascades are involved in a transition to neoplasia, while the decreased activity of androgen receptor (AR) and Wnt pathways contribute to disease progression [ 111 ]. Detailed recognition of pathologic signaling at the molecular level provides the mechanistic background for novel therapeutic approaches ( Figure 3 ).…”
Section: Signal Transduction Pathways As Potential Therapeutic Targetsmentioning
confidence: 99%
“…On this scale, 0 corresponds to the lowest odds, and 100 corresponds to the highest odds in favor of active pathway activity. To identify aberrant STP activity, STP activity scores of healthy postmenopausal fallopian tube epithelium (post‐FTE) were used as a reference for normal activity 26 . Growing evidence suggests a tubal origin of serous borderline tumors and serous LGOC, like in HGSOC 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidence suggests a tubal origin of serous borderline tumors and serous LGOC, like in HGSOC 27 . Post‐FTE scores were used because the hormonal status is similar to that of our study population 26 …”
Section: Methodsmentioning
confidence: 99%
“…2. Ligand dependency: (i) Auto-secretory ligand-dependent activation, in which tumor cells respond to increased expression of their HH ligands in a cell-autonomous manner (i.e., glioblastoma [ 201 ], neck squamous cell carcinoma [ 202 , 203 ], and lung [ 204 ], breast [ 205 , 206 ], ovarian [ 207 ], stomach [ 208 , 209 ], esophageal [ 210 ], pancreatic [ 211 ], and prostate cancers); (ii) Paracrine-ligand-dependent model, in which Hh ligands produced and released by tumor cells switch on HH signaling in the peripheral stroma, in turn facilitating tumor expansion and metastasis, and creating a positive feedback loop (i.e., prostate, ovarian [ 212 – 214 ], pancreatic [ 215 ] and colorectal cancers [ 216 , 217 ]); (iii) Reverse paracrine ligand-dependent signaling activation, indicates that Hh ligands are secreted from the stroma and received by tumor cells (i.e., multiple myeloma, lymphoma [ 218 ], and leukemia [ 219 , 220 ]). 3.…”
Section: Role In Cancer and Therapeutic Strategiesmentioning
confidence: 99%